ENHANCING FUTURE ENGINEERS’ PROFESSIONAL SKILLS THROUGH THE CASE STUDY METHOD (International Educators Conference, 2025)
In a rapidly evolving technological landscape, engineering education must extend beyond theoretical instruction to equip students with the professional skills essential for modern practice. The case study method offers a dynamic approach to cultivate critical thinking, decision making, collaboration, and ethical awareness by immersing learners in realistic engineering scenarios. This article explores how engaging with authentic cases bridges the gap between academic theory and real-world challenges, enabling future engineers to develop the competencies required for successful and responsible professional careers.